A comprehensive review of metasurface structures suitable for RF energy harvesting - Abdulrahman Ahmed Ghaleb Amer (2021)
Energy harvesting (EH) or scavenging is recognized as harvesting energy from ambient energy sources in the surrounding environment. This paper reports a literature review on radio frequency (RF) EH using different metasurface/metamaterial structures based on split-ring resonators (SRRs), electric inductive-capacitive (ELC) resonators, square-patch unit cells, square-ring unit cells, etc. The essential parameters in rectifying antenna (rectenna) design are included, such as receiving antenna efficiency, conversion efficiency, dimensions, supporting substrate properties, frequency band, and overall performance, etc. It is noted that rectenna design using conventional antennas such as microstrip antennas, monopole antennas, slot antennas, dielectric resonator antennas, etc. suffers from low power conversion efficiency with larger size. To overcome the above-mentioned constraints and enhance the conversion efficiency with smaller size, metasurface/metamaterial structures are used as EH collectors. An introduction to EH is discussed, followed by an overview of energy sources in the ambient environment. Several hypothetical and experimental studies on metasurface-based EH systems are summarized.